Terms And Meanings in The Wedding Process of The Ogan Ethnic in Baturaja - Apriyani, Tri Wahyuni (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2024)
Wedding traditions in various regions combine cultural values, religion and customs, which depict deep meaning in the lives of the community. The terms in wedding traditions reflect symbolic meanings in a regional culture. This research investigates the terms and meanings of the traditional wedding process of the Ogan ethnic group in Baturaja. The method used is qualitative with a descriptive approach. The instrument for collecting data used in-depth interview techniques with interview guidelines. There were three respondents in this research using the Snowball Sampling Technique. The data was analyzed by semiotic theory by Ronald Barthes' theory, which analyzes the meaning of denotation and connotation. The results of the research show that there are seven terms, namely Berasan, tipak iban, nampan duo belas, hajat gotong royong, cap-capan and suap-suapan, and the Tanggai dance. Each of these terms has a denotational and connotative meaning in the wedding traditions of the Ogan ethnic group in Baturaja.